Patricia Goldman-Rakic: a pioneer and leader in frontal lobe research - Kolb, Bryan (Frontiers in Human Neuroscience, 2024)
Our understanding of the organizaJon of the frontal cortex can be traced back to the experimental studies in the late 1800s by Fritsch and Hitzig on the frontal cortex of dogs and the frontal cortex of monkeys by Ferrier. These studies and many that followed by others focussed on motor funcJons but half-way through the 20 th century very liQle was understood about the funcJon of the frontal lobe in the control of other behavior, and it was generally thought that the frontal lobe did not play a significant role in cogniJon. One result was that studies of corJcal funcJons in cogniJon were done largely on parietal and temporal corJcal regions with surprisingly liQle interest in the frontal lobe. The first systemaJc studies of the effects of prefrontal lesions nonhuman primates began around 1950, especially by Rosvold and Mishkin in the Laboratory of Psychology at NIMH the USA. With her background in development, Pat Goldman joined this lab in 1965 and began an examinaJon of the effects of prefrontal lobectomy on behavior in infant rhesus monkeys, both during development and later as the animals grew into adulthood. Her developmental studies were ground-breaking as they demonstrated that the effects of early prefrontal lesions varied with the precise age (including prenatal), precise lesion locaJon, behaviors measured, and age at assessment. She also began in parallel extensive studies of the role of the prefrontal cortex for a range of funcJons (especially working memory) in adult monkeys, which led to an examinaJon of factors that influenced funcJonal outcomes acer injury or disease. This research was criJcal in helping to idenJfy the significant role of the prefrontal cortex in cogniJon both in normal brains and in neurological diseases such as schizophrenia. Her pioneering work demonstraJng the role of the prefrontal cortex in cogniJon led to a remarkable increase in the number of researchers studying prefrontal funcJons in both nonhuman primates and rodents. This review will chronical the key findings in her 35+ years studying prefrontal cortex and illustrate the course she set for generaJons to follow.